Overexpression of HER‐2 via immunohistochemistry in canine urinary bladder transitional cell carcinoma ‐ A marker of malignancy and possible therapeutic target. (4th September 2017) - Millanta, F.; Impellizeri, J.; McSherry, L.; Rocchigiani, G.; Aurisicchio, L.; Lubas, G.
Abstract : Transitional cell carcinoma (TCC) is the most commonly diagnosed neoplasm in the urinary bladder. Distant metastases to the regional lymph nodes, lungs, abdominal organs or bones are noted in up to 50% of dogs at time of death. Surgical excision is often not practical as TCC typically involve the trigone of the bladder and/or occurs multifocally throughout the bladder with field cancerization. Therapeutic approaches are very challenging and the requirement to evaluate alternative therapeutic protocols that may prolong survival times in dogs bearing these tumours is compelling. We assessed the immunohistochemical expression of HER‐2 in 23 cases of canine TCCs of the urinary bladder and compare it with non‐neoplastic urothelium in order to evaluate a rationale for targeted therapies and gene‐based vaccines. HER‐2 positivity was recorded in 13/23 (56%) neoplastic lesions. The receptor was significantly overexpressed in neoplastic than in non‐neoplastic samples ( P = .015). According to our preliminary results, it would be of interest to further evaluate the role of HER‐2 in canine TCCs as a marker of malignancy and a therapeutic target for cancer vaccine and antibodies. Moreover, the significantly different overexpression of HER‐2 in TCCs than in non‐neoplastic urothelium further supports to investigate its role in the progression toward malignancy of non‐neoplastic lesions.